2006
DOI: 10.1111/j.1365-2648.2006.03855.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional counselling: an intervention for HIV‐positive patients

Abstract: In the absence of anti-retroviral therapy, high protein nutrition can be an effective intervention for HIV-positive patients in developing countries. The health and nutritional status of the patients can be improved through nutritious food, allowing them to lead longer and better quality lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 11 publications
2
31
1
7
Order By: Relevance
“…This could be attributed to the fact that in the study design, all the groups were given nutritional counseling (Figure 2) in addition to the multivitamin supplementation dispensed to PLWHA receiving care and support at the study centre (SHMCA). The effectiveness of nutritional counseling about protein dietary intake as an intervention to improve health outcomes for HIV positive patients has been reported by Tabi and Vogel [40] whose study; showed increase (from 43.86 kg to 46.57 kg for females and from 51.86 kg to 55.23 kg for males; P = 0.001) in the mean body weight of Ghanaian patients. Similarly, Van Der Sande et al, [41] showed that one unit decrease of BMI resulted in 21% increase in mortality rate (P < 0.001) after controlling baseline immune status (CD4 count).…”
Section: Middle Upper Arm Circumference-muacmentioning
confidence: 61%
“…This could be attributed to the fact that in the study design, all the groups were given nutritional counseling (Figure 2) in addition to the multivitamin supplementation dispensed to PLWHA receiving care and support at the study centre (SHMCA). The effectiveness of nutritional counseling about protein dietary intake as an intervention to improve health outcomes for HIV positive patients has been reported by Tabi and Vogel [40] whose study; showed increase (from 43.86 kg to 46.57 kg for females and from 51.86 kg to 55.23 kg for males; P = 0.001) in the mean body weight of Ghanaian patients. Similarly, Van Der Sande et al, [41] showed that one unit decrease of BMI resulted in 21% increase in mortality rate (P < 0.001) after controlling baseline immune status (CD4 count).…”
Section: Middle Upper Arm Circumference-muacmentioning
confidence: 61%
“…However, now that we are 25 years into the HIV/AIDS epidemic, we can begin to examine these consequences in the context of the effect on food security of affected populations. A troubling contention is made by Tabi and Vogel [43] , nursing investigators working in Ghana: 'In Ghana, like many developing countries, more patients with HIV and AIDS die because of their poor nutritional status than from the disease itself'. Although coming from the two most affluent nations of North America, the text of the 2004 position statement of the dietetics associations of the US and Canada ( table 1 ) [44] Infection with the human immunodeficiency virus (HIV) and the development of acquired immunodeficiency syndrome (AIDS) have had a significant impact on domestic and global health, social, political, and economic outcomes.…”
Section: Food Security and Insecurity In Hiv/aids-affected Communitiesmentioning
confidence: 99%
“…In areas in which antiretroviral therapy is scarce, overcoming dietary intake 20 deficits would have a clear palliative benefit as summarized by Tabi and Vogel [43] : 'The health and nutritional status of the patients can be improved through nutritious food, allowing them to lead longer and better quality lives'. Nutritional support is seen as having the potential to prolong the lives of individuals, both for their own benefit and for those dependent upon them for care [71] .…”
Section: Direct Food Assistance To Mitigate Food Insecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, ahora que han transcurrido 25 años desde el inicio de la epidemia de VIH/SIDA comenzamos a examinar estas consecuencias en el contexto del efecto sobre la seguridad alimentaria de poblaciones afectadas. Tabi y Vogel [43] , investigadores de enfermería que prestan sus servicios en Ghana, expresan un punto de vista inquietante: 'en Ghana, igual que en numerosos países en vías de desarrollo, fallecen más pacientes con VIH y SIDA por su deficiente estado nutricional que por la enfermedad propiamente dicha'. Aunque procedentes de las dos naciones más opulentas de Norteamérica, el texto de la declaración de opinión de 2004 de las asociaciones dietéticas de EE.UU.…”
Section: Seguridad E Inseguridad Alimentarias En Comunidades Afectadaunclassified